Plasma-Chemical Kinetics of Film Deposition in Argon-Methane and Argon-Acetylene Mixtures Under Atmospheric Pressure Conditions - Pothiraja, Ramasamy; Bibinov, Nikita; Awakowicz, Peter (IntechOpen, 2012)
None